PENDIDIKAN KELUARGA DALAM PERSPEKTIF ISLAM - Mariani Mariani (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
The family is an informal educational institution that is first and foremost experienced by children naturally. Parents are responsible for nurturing, caring for, protecting and educating children so that they grow and develop well. Family education is truly an important and decisive center for education, therefore the task of education is to find ways to help parents in the family to be able to educate their children optimally. There are several important things stated in the writing here, namely: Understanding education and family, family functions, relationships within the family, and the formation of the child's personality. Next, it also explains the family from an Islamic perspective based on the Qur'an and the hadiths of the Prophet to form a sakinah, mawaddah warahmah family